Validity and reliability of the measurement of oxygen uptake using the post-exercise breathing method in swimming - a systematic review - Degenhardt, K.; Törpel, A.; Graumnitz, J.; Witt, M. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION Building on the review of Sousa et al. (2014) there are different methods to measure V.O2 in swimming. Here, the post-exercise gas analysis of the V.O2 is an established method to determine the V.O2 during swimming (V. O2swim). To get valid and reliable values of V.O2swim, the used analysis method is of great importance. Therefore, the objective of this work is to systematically review the validity and reliability of the methods used for post-swim gas analysis.